Community Assistance in Pandanrejo Village, Batu for Improving Strawberry Productivity and Quality through the Application of Appropriate Cultivation Technology - Hani Widhianata (Universitas Kristen Cipta Wacana, 2025)
This community service activity was conducted in Pandanrejo village, Batu, one of the centers for strawberry cultivation in West Java. The main problems faced by local farmers include low productivity, inconsistent fruit quality, and limited knowledge in applying efficient and environmentally friendly cultivation technologies. The objective of this activity was to enhance the productivity and quality of strawberries through technical assistance, training, and the application of appropriate cultivation technologies that are easy for the community to implement. The methods included field observations, initial interviews to identify farmers' needs, training on strawberry cultivation based on simple technology (organic mulching, use of biological agents, and drip irrigation systems), and intensive guidance from planting to harvest. Evaluation involved measuring plant productivity, fruit quality (size, color, and total soluble solids content), and farmers responses and adoption levels of the technology. The results demonstrated an average productivity increase of 25% and improved fruit uniformity in terms of size and soluble solids content. Furthermore, farmers gained better understanding of the importance of applying appropriate technologies to maintain input efficiency and environmental sustainability. This activity is expected to serve as a model for similar horticultural commodity empowerment programs in other regions and to strengthen farmers independence in managing strawberry agribusiness based on innovative and sustainable technology.